2020
DOI: 10.1038/s41467-020-16222-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated gut dysbiosis is independent of sexual practice and correlates with noncommunicable diseases

Abstract: Loss of gut mucosal integrity and an aberrant gut microbiota are proposed mechanisms contributing to chronic inflammation and increased morbidity and mortality during antiretroviral-treated HIV disease. Sexual practice has recently been uncovered as a major source of microbiota variation, potentially confounding prior observations of gut microbiota alterations among persons with HIV (PWH). To overcome this and other confounding factors, we examine a well-powered subset of AGEhIV Cohort participants comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 75 publications
11
129
2
Order By: Relevance
“…68 Impaired intestinal barrier integrity is a classical feature of HIV infection, characterized by dysbiosis and increased microbial by-products that drive systemic and mucosal in ammation. 69,70 Microbes with the capacity to catabolize tryptophan have been linked to adverse HIV disease progression, 71 at least in part due to induction of IDO1 that interferes with Th17/Treg balance in the periphery and gut. 72 Our data highlight previously unrecognized interactions between the gut microbiome, its metabolic activity, and HIV persistence.…”
Section: Discussionmentioning
confidence: 99%
“…68 Impaired intestinal barrier integrity is a classical feature of HIV infection, characterized by dysbiosis and increased microbial by-products that drive systemic and mucosal in ammation. 69,70 Microbes with the capacity to catabolize tryptophan have been linked to adverse HIV disease progression, 71 at least in part due to induction of IDO1 that interferes with Th17/Treg balance in the periphery and gut. 72 Our data highlight previously unrecognized interactions between the gut microbiome, its metabolic activity, and HIV persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of P. copri and Prevotella stercorea in PWH has been evaluated in numerous studies and found to be associated with sexual behavior rather than solely HIV status. 47 A few studies examining HIV microbial dysbiosis have been conducted with a majority of men who have sex with men ( MSM). In these studies, there has been an association with sexual orientation and an abundance of Prevotella enterotype in contrast to men who have sex with women who are rich in Bacteroides.…”
Section: Cannabis and The Gut Microbiome In Hivmentioning
confidence: 99%
“…The release of bacterial products provokes a persistent, systemic activation of the innate immune system that triggers and maintains inflammation [34–37]. ART does not completely reverse the damage to the gut mucosal epithelia during early HIV infection nor does it completely restore HIV‐associated microbial dysbiosis [38–41].…”
Section: Drivers Of Immune Dysfunction and Persistent Inflammationmentioning
confidence: 99%